Perception of time in relation to work and private life among Swedish social workers – the temporal clash between the organisation and the individual. Issue 4 (4th July 2019) - Olsson, Eva; Sundh, Mona
ABSTRACT: Time, or rather lack of time, is currently an issue to many involved in social work, in Sweden and elsewhere. Stress at work is presently one of the most common reasons social workers state for leaving their profession or their workplace. This article examines how time is perceived in relation to work and private life by employees in the social services. The investigation was conducted as a qualitative interview study with six social workers. An abductive approach was adopted in the analysis. The results indicate a general experience of lack of time and an individual perception of time among the interviewees. What they say about time indicates that they have a monochronic perspective on time. It is also shown that the respondents use different curbing strategies to recuperate. At work, strategies take the form of creating recovery arenas allowing for micropauses such as eating an apple or having a cup of coffee. After work, exercising or strolling in the woods are common strategies. In relation to the employer and the organisation individuals also assume responsibility for organisational shortcomings that they cannot influence.